EVALUASI PERATURAN DAERAH KABUPATEN PONTIANAK NOMOR 5 TAHUN 2008 TENTANG PENDIRIAN PT. PELABUHAN KUALA MEMPAWAH KABUPATEN PONTIANAK - Muhammad Alfaini E. 01109054 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Port Development Kuala Mempawah unfinished process may impact not established Pontianak Regency Regulation No. 5 of 2008 on the establishment of PT. Kuala Mempawah port. This study aims to find out information about the performance of the implementor and describe the factors that affect the implementation of law No. 5 of 2008 on the Establishment of PT. Kuala Mempawah-port Pontianak regency.In this study, the implementation of local regulations Pontianak District No. 5 of 2008 on the establishment of PT. Kuala Mempawah harbor seen from the construction and port activity. This study uses qualitative descriptive type of research is aimed at describing the classified objects studied by exploring the facts and data. The data collection instruments are researchers themselves, while the researchers used three tools, namely: observation, interviews and document / records. The results of the writing of this article is the performance of the implementor Kuala Mempawah port development is still relatively low. Development of implementation guidelines Port Kuala inconsistent because it is not equipped with a feasibility study and coordination between relevant agencies is still not optimal. Limited sources of funding, given the construction of the port of Kuala Mempawah a national port, it requires huge funding to make it happen. Advice from researchers as follows: should the parties regarding the conduct of port development Kuala Mempawah should conduct an evaluation of the development policy of the Port of Kuala Mempawah thoroughly, involving decision makers, both executive and legislative. Kuala Mempawah with establishment of the port should be done consistently. And must perform a feasibility study of the construction of the Port of Kuala.Keywords: Evaluation, Implementation and Performance